2014 IEEE Metrology for Aerospace (MetroAeroSpace) 2014
DOI: 10.1109/metroaerospace.2014.6865964
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of lander effects on DREAMS scientific package measurements

Abstract: The DREAMS (Dust characterisation, Risk assessment and Environment Analyser on the Martian Surface) sensor suite is designed to investigate Martian meteorology and atmospheric electric properties at the ExoMars 2016 EDM (Entry, Descent and landing demonstrator Module) landing site. The DREAMS package will provides wind speed and direction measurement by means of MetWind hot-film anemometer and near surface temperature by means of MarsTem resistance thermometer sensor. The aim of this work is to investigate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In the future, to improve the accuracy of the noise estimations, more detailed Computational Fluid Dynamics simulations could be performed to model the wind-lander interactions (e.g., Chiodini et al 2014;Gendron et al 2010). However, the atmospheric boundary layer is itself fully and highly turbulent, and the lander induced eddies are just one component of the full spectrum that the boundary layer itself presents.…”
Section: Parametermentioning
confidence: 99%
“…In the future, to improve the accuracy of the noise estimations, more detailed Computational Fluid Dynamics simulations could be performed to model the wind-lander interactions (e.g., Chiodini et al 2014;Gendron et al 2010). However, the atmospheric boundary layer is itself fully and highly turbulent, and the lander induced eddies are just one component of the full spectrum that the boundary layer itself presents.…”
Section: Parametermentioning
confidence: 99%
“…In addition, from the retrieved titanium structure time constant, the secondary thermometer will support the correction of errors introduced by solar radiation contribution on the primary sensor. Chiodini et al (2014) showed that the radiative contribution of the thermal flux on the sensor is lower than the 30% at noon conditions (the worst from this point of view) with a wind of 1m/s and that this contribution decreases to 20% with a 5 m/s wind.…”
Section: Marstemmentioning
confidence: 92%
“…Missus allowed the validation of the mathematical model (even of sun irradiance effects) and the tuning of the electrical current profile in order to maximize sensitivity/self-heating ratio and the overall SNR. To infer MarsTEM performance from MISSUS experiment results, the comparison between Earth and Mars potential temperature was performed (Chiodini et al, 2014).…”
Section: Marstemmentioning
confidence: 99%
See 1 more Smart Citation